Study of lumbar spine activity regularity based on Kanade-Lucas-Tomasi algorithm. (March 2019) - Wang, Lu; Zhang, Yafeng; Lin, Xiaohong; Yan, Zheng
Highlights: Accuracy of the average errors achieved for displacement and angle of KLT - based algorithm were high. Quantitative fluoroscopy (QF) can obtain continuous, dynamic image sequences of lumbar motion at low radiation doses. More smoothness and stability in the intervertebral kinematics parameters were obtained by KLT - based algorithm. Abstract: The diagnosis of lumbar spine pathologies such as lower back pain (LBP) is extremely difficult, and a consensus regarding a diagnostic standard has not yet been reached. Accurate measurement of intervertebral kinematic parameters helps to understand the etiology and diagnosis of related diseases, and to evaluate the subsequent treatment. Quantitative fluoroscopy (QF) which can obtain continuous, dynamic image sequences of lumbar motion at low radiation doses were introduced. The estimation of intervertebral kinematics depends on the precise localization of lumbar vertebrae. Usually, vertebral corners are identified and tracked by automated methods or manual method. This study presents a novel method for vertebral tracking based on the KLT (Kanade-Lucas-Tomasi, KLT) algorithm for intervertebral kinematics analysis. Accuracy of the proposed method was tested using a sagittal human image which contained two vertebral bodies, and the average errors achieved for displacement and angle were within 0.25 mm and 0.3°, respectively. To test the proposed method under clinical conditions, totally 11 volunteers were recruited and a result of more smoothness and stability in the intervertebral kinematics was obtained with comparing to the manual method by an experienced and trained clinician. In conclusion, the proposed method is an effective, accurate way to assess lumbar vertebrae tracking.